An explorative study of the perceptions of social workers who are exposed to work-related, secondary traumatic experiences through their clientele, of the psychosocial support Equine Assisted Therapy (E.A.T) could provide - Garland, Sarah (Department of Social Development, 2014)
Includes abstract.